The Praeger handbook of environmental health / edited by Robert H. F riis. - Friis, Robert H. (Santa Barbara, Calif. : Praeger, 2012)
"Written by internationally acclaimed experts in the United States a nd abroad, this comprehensive set of environmental health articles serv es to clarify our impending challenges as well as opportunities for cha nge"--
v. 1. Foundations of the field.
Includes bibliographical references and index.
Keywords: Environmental health -- Handbooks, manuals, etc